2015
DOI: 10.1111/bju.13314
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer risk prediction using the novel versions of the European Randomised Study for Screening of Prostate Cancer (ERSPC) and Prostate Cancer Prevention Trial (PCPT) risk calculators: independent validation and comparison in a contemporary European cohort

Abstract: All men who underwent a transrectal prostate biopsy in a European tertiary care centre between 2004 and 2012 were retrospectively identified. The probability of detecting prostate cancer and significant cancer (Gleason score ≥7) was calculated for each man using the novel versions of the ERSPC-RC (DRE-based version 3/4) and the PCPT-RC (version 2.0) and compared with biopsy results. Calibration and discrimination were assessed using the calibration slope method and the area under the receiver operating charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 33 publications
9
77
0
Order By: Relevance
“…Asides from the validatory nature of this paper [1], there are several other findings though less novel, which are further important additions to the urological literature.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Asides from the validatory nature of this paper [1], there are several other findings though less novel, which are further important additions to the urological literature.…”
mentioning
confidence: 71%
“…
Poyet et al [1] have performed the largest external validation of the European Randomised Study for Screening of Prostate Cancer (ERSPC) and Prostate Cancer Prevention Trial (PCPT) v2.0 risk calculators (RCs) to date, having retrospectively identified 1996 men undergoing prostate biopsy in a Swiss tertiary care facility.Asides from the validatory nature of this paper [1], there are several other findings though less novel, which are further important additions to the urological literature.This study confirms the superior discriminative performance of multi-factorial RCs over PSA alone in the assessment of prostate cancer: where the area under the receiver operating characteristic curve (AUC) for the prediction of significant prostate cancer for PSA alone was 0.65, comparing less favourably than 0.73 and 0.70 for the ERSPC and PCPT v2.0 RCs, respectively.The authors performed sensitivity analysis showing higher detection rates for prostate cancer (29.4% vs 18.1%) and significant prostate cancer (15.9% vs 5.9%) in patients receiving a 12-core biopsy than in those receiving a 6-8 core biopsy.Supplementary analysis by the authors evaluated the performance of previous versions of the PCPT-RC, specifically v1.0 and PCPT-RC v1.0 with prostate volume. The inclusion of prostate volume demonstrated an improved predictive ability of this RC.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[62] Smaller studies confirmed performance of multivariate prediction over a PSA and DRE based algorithms. [63, 64]…”
Section: Methodsmentioning
confidence: 99%
“…Although all of these calculators can be used to estimate the risk of harbouring clinically significant prostate cancer prior to prostate biopsy, they again display only moderate predictive accuracy, which varies across different study populations. 88,[93][94][95][96] Nonetheless, their online availability, ease of use, and improvement upon PSA alone make them attractive adjuncts when counselling patients considering undergoing prostate biopsy. Thus, prostate risk calculators can be used to estimate the risk of clinically significant prostate cancer in men presenting with an elevated PSA.…”
Section: Prostate Risk Calculatorsmentioning
confidence: 99%